PedsCases - A Learning Module for Interpretation of Pediatric Abdominal X-Ray for Medical Students - Jake Hayward; Peter Gill; Jacqueline Lee; Bryan Dicken (Association of American Medical Colleges, 2012)
Abstract This learning module features four multistep clinical cases that review an approach to abdominal X-ray for medical students. The cases go through a 4-month-old presenting with intussusception, an 18-month-old with small bowel obstruction, an 8-year-old with pneumatosis intestinalis, and a 4-year-old with appendicitis. Each case includes several radiographical images and management considerations. This module is a part of PedsCases, a series of comprehensive web-based educational tools that focus on the core objectives of undergraduate pediatric education with extensive student involvement. PedsCases was created for and by medical students and provides an opportunity for active self-directed learning in pediatrics. The learning modalities available include questions, flash card-type quizzes, multistep clinical cases, and podcasts. PedsCases has been used in 96 different countries, and there have been over 10,000 downloads of the available podcasts.